2020
DOI: 10.14295/bds.2020.v23i1.1822
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the quality of root canal filling and instrumentation time using kedo-s files, reciprocating files and k-files

Abstract: Objective: Pulpectomy is the conservative treatment approach that retains and preserves the primary tooth in the dental arch in its normal function and non-pathologic state until its exfoliation. Over the years, pulpectomy has been performed using various instrumentation techniques. The aim of this study was to compare the quality of root filing and instrumentation time using Kedo-S files, Reciprocating files and K-files in primary teeth. Material And Methods: A randomized clinical trial was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 14 publications
2
32
2
1
Order By: Relevance
“…Parents and children should work together to maintain good oral hygiene. Good attitude of parents re lects as good oral health in children and vice versa (Gurunathan and Shanmugaavel, 2016;Lakshmanan et al, 2020). Preservation of primary teeth in the dental arch is important for optimal position of permanent teeth.…”
Section: Resultsmentioning
confidence: 99%
“…Parents and children should work together to maintain good oral hygiene. Good attitude of parents re lects as good oral health in children and vice versa (Gurunathan and Shanmugaavel, 2016;Lakshmanan et al, 2020). Preservation of primary teeth in the dental arch is important for optimal position of permanent teeth.…”
Section: Resultsmentioning
confidence: 99%
“…(Moghaddam et al, 2009;Musale, 2013;Ramezanali et al, 2015;Katge et al, 2014;Azar et al, 2012) Study done by (Jeevanandan and Govindaraju, 2018) concluded that clinical use of paediatric rotary iles Kedo-S was effective during root canal preparation of primary teeth with a reduction in instrumentation time and better quality of obturation. (Lakshmanan et al, 2020) The challenges faced in this study is that not many studies have been done on this topic and some studies have shown that they found no signi icant difference in cleaning ef icacy at middle and apical thirds, but the cervical third was more effectively cleaned with hand K iles. The purpose of this research is to collect more data on the preference of pediatric dentists on hand or rotary instruments which gives us better and ef icient root canal therapy resulting in patient satisfaction.…”
Section: Introductionmentioning
confidence: 91%
“…Further, primary teeth play an imperative role in the self esteem of the preschool children and also plays a pivotal role in speech development, esthetics and function (Ravikumar et al, 2017). Restoration of the primary molars is thus essential before it becomes grossly decayed and the choice of treatment left is pulpectomy (Jeevanandan and Govindaraju, 2018), to treat the necrosed pulp due to caries (Lakshmanan et al, 2020). Further, Pulpectomy is challenging and time consuming (Govindaraju et al, 2017b) and it is the only choice left to save the teeth from extraction and maintain its form and function (Govindaraju et al, 2017c) Thus it is better to restore it in early stages of disease using materials such as GIC and composites.…”
Section: Figure 1: Pie Chart Representing the Distribution Of Gic Andmentioning
confidence: 99%